Effect of Gibberellin, Foliartal Foliar Fertilizer and Growing Medium in Content of Mineral and Organic of Oleander Plant - D. A. K., Jamil; A. A., Yaseen (Al-Qadisiyah Journal of Pure Science, 2018)
A pot experiment was conducted in a plantation affiliated to the Al-Diwaniya city during winter season (2012 – 2013) to find out effects of gibberellin, foliartal foliar fertilizer and growing medium in content of mineral and organic of oleander plant leaves (Nerium oleander L.). The design of the experiment was randomized complete blocks (RCBD) in a factorial arrangement with three replicate in organizing the workers for the three factors, first factor included four concentrations of gibberellin (0, 250, 500 and 750) mg. L-1, the second factor included four concentrations of Foliartal foliar fertilizer (0, 250, 500 and 750) ml. L-1, the third factor included three growing medium (1 patmos: 2 sand, 1 patmos: 2 clay and 1 patmos: 2 silt). Means were compared by using averages revised least significant difference (RLSD) at 0.05 probability level. Results revealed that: 1- The percentages of N, P, K, Ca, total protein, organic matter recording by used of GA3 (750 mg. L-1). 250 mg. L-1 of GA3 was superior with Mg%. 2- The foliar fertilizer by the concentration of 750 ml. L-1 increased of N%, total protein% and organic matter%. 500 mg. L-1 of foliar fertilizer increased of P%, Ca%. Increased of K% and Mg% had the effect of a 250 mg. L-1 foliar fertilizer concentration. 3- Growing medium (1 patmos:2 silt) increased of N%, total protein%, Mg% and organic matter% in the leaves. Soil type (1 patmos:2 clay) increased K% while growing medium (1 patmos:2 sand), significantly increased of P% and Ca% in the leaves. 4- The interaction between GA3 and foliar fertilizer by combinations of (250 mg.L-1 GA3 and 750 ml. L-1 foliar fertilizer, or versa) increased in most studied characters of oleander plant. 5- Interaction between Growing medium and GA3 recorded of the highest rates for the majority of traits in plants cultured in soil type (1 patmos:2 sand) or (1 patmos:2 silt) and spryer with 750 or 250 mg. L-1 of GA3. 6- Foliar fertilizer by 750 ml. L-1 and soil type (1 patmos:2 silt) superior in N%, total protein% and organic matter%. The combinations of 750 ml.L-1 fertilizer with growing medium (1 patmos:2 sand) that superior with ​​ P%. The combination of 500 ml. L-1 foliar fertilizer with growing medium (1 patmos:2 sand) increased of Ca%. The concentration of 250 ml. L-1 with soil type (1 patmos:2 silt) increased Mg%, while the combination of 250 ml. L-1 foliar fertilizer with growing medium (1patmos: 2 clay) increased K%. 7- Triple interaction between the factors revealed a significant improvement of the oleander plant in most traits, especially with the combinations constituent of GA3 and foliar fertilizer concentrations with medium of (1 patmos: 2 silt).